2017
DOI: 10.1111/exd.13308
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf‐1 is involved in dexamethasone‐mediated hair follicle regression

Abstract: The stress-related neurohormones including glucocorticoids (GCs) are secreted by hair follicles (HFs), and GCs suppress murine hair growth in vivo. In this study, we found that dexamethasone (Dex), a synthetic GC, increased the expression of dickkopf-1 (Dkk1), a known catagen inducer, in dermal papilla (DP) cells, but not in follicular keratinocytes. The neutralizing Dkk1 antibody significantly attenuated the Dex-induced inhibition of human hair shaft elongation. In addition, the neutralizing Dkk1 antibody del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
0
28
1
Order By: Relevance
“…These results suggested that hUcB-MScs may prevent hair catagen by suppressing dKK-1 expression. Although a previous study indicated that dex increased dKK-1 secretion from hdPcs followed by outer root sheath apoptosis, this did not confirm that Dex directly influences keratinocyte cell death (37). The results of the present study demonstrated that dex inhibited cell proliferation, followed by the induction of keratinocyte apoptosis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results suggested that hUcB-MScs may prevent hair catagen by suppressing dKK-1 expression. Although a previous study indicated that dex increased dKK-1 secretion from hdPcs followed by outer root sheath apoptosis, this did not confirm that Dex directly influences keratinocyte cell death (37). The results of the present study demonstrated that dex inhibited cell proliferation, followed by the induction of keratinocyte apoptosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Topical administration of dex causes hair follicle degeneration, thus indicating the clinical phenotype of the catagen phase (36). In addition, dex application increased dKK-1 protein expression levels in human dermal papilla cells, which was followed by hair follicle apoptosis (37). dKK-1 acts as an antagonist of the Wnt/β-catenin pathway, and secretory dKK-1 induces apoptosis of follicular keratinocytes (38).…”
Section: Discussionmentioning
confidence: 99%
“…This boost in Wnt signalling enhances human hair shaft formation and inhibits catagen entry. Therefore, Dickkopf-related protein 1 (DKK1) is not the only important regulator of Wnt activity in the human HF [ 34 ], and SFRP1 is a viable alternative target molecule for the therapeutic up-regulation of hair growth–promoting Wnt signalling.…”
Section: Resultsmentioning
confidence: 99%
“…DKK1 and NKD1 are antagonistic inhibitors of the canonical Wnt signaling pathway [ 42 , 43 ]. DKK1 also has an inhibitory effect on the differentiation of mesenchymal stem cells to fibroblasts [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%